Thomas and the jet engine: thomas & friends - Awdry, W. (Egmont London, 2008)
In "Thomas and the Jet Engine," Thomas, the little blue engine, gets a chance to be as fast as his hero, Gordon. He is tasked with transporting a jet engine to the airfield. Excited about the prospect of speed, Thomas rushes through his task, neglecting safety and causing a minor accident.